The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12985-021-01682-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and clinical characteristics of human bocavirus infection in infants and young children suffering with community acquired pneumonia in Ningxia, China

Abstract: Background Pneumonia has a high incidence rate and is a major cause of mortality in children, mostly community-acquired pneumonia (CAP). Human bocavirus (HBoV), since it first identified in 2005, has been repeatedly associated with respiratory tract infections. Nevertheless, the role and related information of HBoV as a pathogen of CAP has not been fulfilled. Here our study is to assess the epidemiological and clinical features in HBoV-positive children with CAP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
19
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 55 publications
8
19
3
Order By: Relevance
“…The differences observed between the pathogen etiology and clinical characteristics of HBoV-positive and HBoV-negative patients are presented below. HBoV, RSV, and HRV were detected in high frequencies in both groups, which is in agreement with previous studies (Madi and Al-Adwani, 2020 ; Ji et al, 2021 ; Nantachit et al, 2021 ). As indicated in the results, HBoV infection was more common in children ≥ 5 years old as opposed to most studies at this stage where HBoV1 is more prevalent in children under 2 years of age.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The differences observed between the pathogen etiology and clinical characteristics of HBoV-positive and HBoV-negative patients are presented below. HBoV, RSV, and HRV were detected in high frequencies in both groups, which is in agreement with previous studies (Madi and Al-Adwani, 2020 ; Ji et al, 2021 ; Nantachit et al, 2021 ). As indicated in the results, HBoV infection was more common in children ≥ 5 years old as opposed to most studies at this stage where HBoV1 is more prevalent in children under 2 years of age.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that children ≥5 years old should be considered a priority study group, since this group has relatively higher immunity than children under 2 years old, which might help identify more risk factors for HBoV1 infection in different immune populations. In patients with HBoV infection, respiratory symptoms, such as cough, rales, or wheezing, remain the most common symptoms, which are consistent with previous reports (Ji et al, 2021 ; Zhang et al, 2021 ). In HBoV-positive patients, AST, LDH, URE, CK-MB, and Mg levels were significantly different from those in HBoV-negative patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The experiment also showed that Gram-positive bacteria were the main strain detected before and after pandemic onset, and the top three bacteria were Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus , which was in accordance with the results of Nathan et al [ 15 ] and Mathew [ 16 ] but was inconsistent with the results of Ji et al [ 17 ] and Liu et al [ 18 ], who reported that Gram-negative bacteria were the most common agents. Klebsiella pneumoniae was the most common bacteria.…”
Section: Discussionsupporting
confidence: 54%